Arahan Perluasan Kawasan Pasar Simpang Dago Berdasarkan Rencana Tata Ruang Kota Bandung - Deby Shafa Anifa; Ira Safitri Darwin (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. Traditional markets are synonymous with negative stigma, such as dirty, disorderly places, minimal facilities, and the character of places that are prone to fraud. Simpang Dago market in the city of Bandung, which has a negative stigma, is also affected by the problems of irregular street vendors, traffic, and trade zoning. Simpang Dago Market revitalization has been carried out several times, but has not produced a significant impact. In fact, the revitalization in 2015 and 2019 has not resolved the problem of irregular street vendors, traffic, and trade zoning. The planned outputs in the Bandung City RDTR 2015–2035 and Bandung City RTRW 2022–2042 direct the expansion of the trade and service area in the Simpang Dago area. This has the potential to deal with problems that have not ended yet, by expanding Simpang Dago Market area inward which currently has an area of 3,610.05 m². The expansion of the Simpang Dago Market area has not been determined and studied further, so this research is important to overcome the irregularity problem. Calculations for the expansion of the Simpang Dago Market area in Bandung City used a mixed methods approach with descriptive and spatial (GIS-based) analysis methods. The results showed that Simpang Dago Market area could be planned for an inward expansion of 10,680 m² with an increase in the market classification to type II according to SNI 8152:2021 Public Market. Abstrak. Pasar tradisional identik dengan stigma negatif, seperti tempat yang kumuh, kotor, tidak beraturan, fasilitas yang minim, serta karakter tempat yang rawan terjadi kecurangan. Pasar Simpang Dago Kota Bandung dengan stigma negatif tersebut turut terdampak permasalahan ketidakteraturan PKL, lalu lintas, serta zonasi perdagangan. Revitalisasi Pasar Simpang Dago sudah beberapa kali dilakukan, tetapi belum menghasilkan dampak yang signifikan. Bahkan, revitalisasi di tahun 2015 dan 2019 belum mengatasi permasalahan ketidakteraturan PKL, lalu lintas, serta zonasi perdagangan tersebut. Keluaran rencana dalam RDTR Kota Bandung Tahun 2015–2035 dan RTRW Kota Bandung Tahun 2022–2042 mengarahkan perluasan kawasan perdagangan dan jasa di kawasan Simpang Dago. Hal ini menjadi potensi untuk menangani permasalahan yang selama ini belum berakhir, yakni dengan perluasan kawasan Pasar Simpang Dago ke arah dalam yang secara eksisting memiliki luas sebesar 3.610,05 m². Perluasan kawasan Pasar Simpang Dago belum ditentukan dan diteliti lebih lanjut, sehingga penelitian ini menjadi penting untuk mengatasi permasalahan ketidakteraturan tersebut. Perhitungan untuk perluasan kawasan Pasar Simpang Dago Kota Bandung menggunakan pendekatan mixed methods dengan metode analisis deskriptif dan spasial (GIS-based). Hasil penelitian menunjukkan bahwa kawasan Pasar Simpang Dago dapat direncanakan perluasan ke arah dalam sebesar 10.680 m² dengan peningkatan klasifikasi pasar menjadi tipe II sesuai SNI 8152:2021 Pasar Rakyat.